Combined Military Hospital Quetta/National University of Medical Sciences (NUMS) Pakistan - Khan, Muhammad Ijaz; Haider, Ghulam; Ahmed, Khalil; Shaikh, Shiraz; Abbas, Kiran; Ahmed, Moiz; Sohail, Hamza (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To evaluate the tumor grades in different receptors (Estrogen, Progesterone and Her-2/neu) categories and age groups among women with Breast Cancer.Study Design: An observational cross-sectional study.Place and Duration of Study: Oncology department, Jinnah Postgraduate Medical Center, Karachi, from Jul 2017 to Dec 2018.Methodology: Total of 450 patients were enrolled in this study using non-probability consecutive sampling technique. The Receptors Status of Estrogen, Progesterone and Her2/neu was resolved into 4 different categories as i) Triple Positive (ER+PR+HER2+), ii) Triple Negative (ER-PR-HER2-), iii) ER+PR+Her2-, iv) ER–PR-Her2+. Age-wise, patients were divided into 3 groups.Results: The mean age of patients was 46.57 years ± 10.82. No patient was observed with Grade I tumor while 240 with Grade II and 210 with Grade-III. 164/450 patients were observed in the ER+PR+Her2- category. Out of 164, 68.3% were Grade-II and 31.7% were Grade-III (p˂0.001). In Triple-Negative category, 94 patients were observed, 31.90% were Grade-II while 68.10% were Grade-III (p